ANALISIS PENDAPATAN USAHATANI PADI SAWAH SISTEM TAPIN DI DESA BALINGGI JATI KECAMATAN BALINGGI KABUPATEN PARIGI MOUTONG - Damayanti, Astrid; Alam, Max Nur; Effendy, Effendy (AGROTEKBIS, 2019)
This study aims to find out how much income of the paddy rice farmer of tapin system. This research was conducted in Balinggi Jati Village, Balinggi Sub-District, Parigi Moutong Regency, the location of the research was done by purposive sampling. This research was conducted in February until April 2017. The number of rice farmers of tapin system as many as 210 people, with the number of samples 30 people using a simple random sampling method. The result showed that the average income received by farmers in paddy field system in Balinggi Jati Village is Rp7.056.115/MT, with the average land area owned by respondents is 1.96 ha.